Meanwhile On Earth: Irony and Simulacra in Elvira Hernández’s ¡Arre! Halley ¡Arre! (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
From the media manipulation prompted by the Chilean dictatorship during the months prior to the sighting of Halley's comet, this article reads the irony present in the poetry collection of Elvira Hernández‟s !Arre! Halley! Arre! (1986) as a strategy that aims at not only confirming the identity of a fractured community, but also at criticizing the dictatorial intention to assimilate the success of emerging neoliberal policies with “unique and unrepeatable” astronomical sightings.
Keywords: Elvira Hernández; Irony; Post-dictatorship; Simulacrum